2014
DOI: 10.1111/pce.12327
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of leaf water relations components in co‐occurring iso‐ and anisohydric conifer species

Abstract: Because iso- and anisohydric species differ in stomatal regulation of the rate and magnitude of fluctuations in shoot water potential, they may be expected to show differences in the plasticity of their shoot water relations components, but explicit comparisons of this nature have rarely been made. We subjected excised shoots of co-occurring anisohydric Juniperus monosperma and isohydric Pinus edulis to pressure-volume analysis with and without prior artificial rehydration. In J. monosperma, the shoot water po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
127
2
6

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(140 citation statements)
references
References 63 publications
(74 reference statements)
5
127
2
6
Order By: Relevance
“…However, our conclusion that these traits are independent is based on interspecific differences in average trait values. Intraspecific variation in both of these traits was relatively low in our study, but other studies have demonstrated notable intraspecific variation in stem P50 (Love et al , ) and osmotic adjustments to leaf TLP (Meinzer et al , ; Maréchaux et al , ; Nolan et al , ; Johnson et al , ). Future tests of this relationship should account for both interspecific differences and intraspecific variation to gain a multiscale perspective on the strength of integration between stem P50 and leaf TLP.…”
Section: Discussioncontrasting
confidence: 67%
“…However, our conclusion that these traits are independent is based on interspecific differences in average trait values. Intraspecific variation in both of these traits was relatively low in our study, but other studies have demonstrated notable intraspecific variation in stem P50 (Love et al , ) and osmotic adjustments to leaf TLP (Meinzer et al , ; Maréchaux et al , ; Nolan et al , ; Johnson et al , ). Future tests of this relationship should account for both interspecific differences and intraspecific variation to gain a multiscale perspective on the strength of integration between stem P50 and leaf TLP.…”
Section: Discussioncontrasting
confidence: 67%
“…The anisohydric behavior of Q. ilex observed here is at odds with the general view considering this species as isohydric [27], even in studies conducted in a nearby valley in the same study area [33,47]. Importantly, the iso-/anisohydric dichotomy does not account for differences in vulnerability to xylem embolism [12], nor for leaf traits involved in turgor regulation [65]. Given the current methodological controversy on the measurement of vulnerability to xylem embolism (e.g., [48,61]) we cannot be sure that the extremely high PLC values estimated here are real.…”
Section: Contrasting Hydraulic Strategies In P Sylvestris and Q Ilexcontrasting
confidence: 54%
“…Species with deeper roots can access water at greater depths than are unavailable to more shallowly rooted species (Jackson et al, ; Canadell et al, ). Different species exhibit a spectrum of traits that vary in cavitation risk across all three of these axes of hydraulic control (Figure ; Meinzer, Woodruff, Marias, McCulloh, & Sevanto, ).…”
Section: Introductionmentioning
confidence: 99%